Is Nasal Septum–Tragus Length Measurement Appropriate for Endotracheal Tube Intubation Depth in Neonates? A Randomized Controlled Study - Uygur, Özgün; Öncel, Mehmet Yekta; Şimşek, Gülsüm Kadıoğlu; Okur, Nilüfer; Çelik, Kıymet; Bozkurt, Özlem; Yücesoy, Ebru; Terek, Demet; Arslan, Meltem Koyuncu; Pekçevik, Yeliz; Akar, Melek; Köroğlu, Özge Altun; Oğuz, Suna; Kültürsay, Nilgün (American Journal of Perinatology, 2019)
Objective Endotracheal intubation is a frequent procedure performed in neonates with respiratory distress. Clinicians use different methods to estimate the intubation insertion depth, but, unfortunately, the improper insertion results are very high. In this study, we aimed to compare the two different methods (Tochen's formula = weight in kilograms + 6 cm; and nasal septum–tragus length [NTL] + 1 cm) used to determine the endotracheal tube (ETT) insertion depth.Study Design Infants who had intubation indications were enrolled in this study. The intubation tube was fixed using the Tochen formula (Tochen group) or the NTL + 1 cm formula (NTL group). After intubation, the chest radiograph was evaluated (above T1, proper place, and below T2).Results A total of 167 infants (22–42 weeks of gestational age) were included in the study. The proper tube placement rate in both groups was similar (32.4 vs. 30.4% for infants < 34 weeks of gestational age and 56.8 vs. 45.0% in infants > 34 weeks of gestational age). The ETT was frequently placed below T2 at a higher rate in infants with a gestational age of <34 weeks, especially in the NTL group (46% in the Tochen group and 60.7% in the NTL group).Conclusion The NTL + 1 cm formula led to a higher rate of ETT placement below T2, especially in infants with a birth weight of <1,500 g. Therefore, more studies are needed to determine the optimal ETT insertion depth.
Keywords: endotracheal tube placement; intubation; nasal septum–tragus length; newborn